OPTIMIZING THE ROLE OF INKING UNIT IN OFFSET PRINTING MACHINE - Juliandri .; Anton Hadiwijaya; Yessy Yerta Situngkir (Politeknik Negeri Media Kreatif, 2019)
In-depth observations have been made on the printing process using the Heidelberg Speedmaster CD 102 machine. In this process, the ink unit becomes the biggest concern because of its role in the quality of the printout. Observations are made directly in the field on routine procedures carried out and discuss events in the field to identify problems and determine actions. The results of the study indicate that there are several things that must be improved related to the routine maintenance schedule, the technical setup of the inking unit and identification of potential problems as a reference for improving standard operations in the field.Keywords—Inking unit, offset printing machine, speedmaster machine